Resident jaguars (Panthera onca) at the heart of the Maya Forest in Guatemala - Carlos A. Gaitán; Vivian Roxana González-Castillo; Gerber Daniel Guzmán-Flores; Pablo Andrés González-Xiloj; Usi'j Tz'nunja' Bá; Rony A. García-Anleu; Manolo José García (Revista Mexicana de Biodiversidad)
In this study we determined the resident status of individual jaguars (Panthera onca) in a 7-year timeframe, in order to provide insight into the life history of this species as an input for abundance estimations and the management of the Maya Forest shared by Guatemala, Mexico, and Belize. We gathered photographic jaguar records from studies conducted in 2 Core Zones of the Maya Biosphere Reserve from 2013 to 2019. Individual jaguars were identified by their unique coat pattern, and were considered as residents when recorded for 3 or more consecutive years. Also, range sharing and interactions were quantified. Both female and male resident individuals were recorded. We suggest the presence of a resident population with a tendency for spatial or temporal range exclusion within individuals from the same sex and a fast male’s turnover, and a demographically mixed group of transients. These circumstances appoint the relevance to determine the resident status of individuals for accurate abundance estimations and population trends, and also in maintaining the integrity of the transboundary continuous forest cover, as connectivity appears to have an important role for maintaining the fluctuating jaguar population dynamics.